Visualisation of Perception of Experiential Activities in Business and Administration and Economy - Rosaura Fernández-Pascual; Ana Marín Jiménez; María Pilar Fernández- Sánchez (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
This paper explores how to incorporate information visualization tools into qualitative studies to represent the underlying structure of knowledge. Information visualization plays a key role in many areas such as decision-making, data mining, market studies, or knowledge management. A case of experiential learning was developed for Quantitative Techniques in Business and Administration and Economy Degrees at the University of Granada, Spain. The goal is to analyze the opinion of students (n = 227) on the development of the activity through information visualization techniques. The gathered information was subjected to a categorization process to unify and homogenize the responses. After a term-clumping process, a co-word analysis using the VosViewer software is used to analyze the relationships among terms and provide the network maps. Results display the main associations and clusters of terms used when assessing the experiential activity, using qualitative techniques. In conclusion, the strengths of data visualization enabling a better understanding of data for qualitative studies are established.
Keywords: O30; A22; C88; Y91; 330; information visualization; term-based method; experiential learning; knowledge; quantitative techniques